2013
DOI: 10.1016/j.bone.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Fracture healing with alendronate treatment in the Brtl/+ mouse model of osteogenesis imperfecta

Abstract: Osteogenesis imperfecta (OI) is a heritable bone dysplasia characterized by increased skeletal fragility. Patients are often treated with bisphosphonates to attempt to reduce fracture risk. However, bisphosphonates reside in the skeleton for many years and long-term administration may impact bone material quality. Acutely, there is concern about risk of non-union of fractures that occur near the time of bisphosphonate administration. This study investigated the effect of alendronate, a potent aminobisphosphona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Using the oim / oim mouse model for OI (which is null for c ol1a2 ), Delos et al (2008) found no significant differences in between oim / oim and WT in callus size or mineralization, as well as no differences in fractured and contra-lateral intact bones. However, using the Brtl/+ mouse model for OI (which is a “knockin” of Col1a1 Gly 349 to Cys), Meganck et al (2013) found decreased callus stiffness as well as decreased energy to failure, angular displacement to failure and ultimate torque at failure in the Brtl/+ mice compared to WT. More interestingly, they found that 5 weeks post-fracture the Brtl/+ fractured bones had a significant increase in energy to failure compared to intact contralateral bones, suggesting the callus they produced is actually stronger than their intact bone.…”
Section: Discussionmentioning
confidence: 97%
“…Using the oim / oim mouse model for OI (which is null for c ol1a2 ), Delos et al (2008) found no significant differences in between oim / oim and WT in callus size or mineralization, as well as no differences in fractured and contra-lateral intact bones. However, using the Brtl/+ mouse model for OI (which is a “knockin” of Col1a1 Gly 349 to Cys), Meganck et al (2013) found decreased callus stiffness as well as decreased energy to failure, angular displacement to failure and ultimate torque at failure in the Brtl/+ mice compared to WT. More interestingly, they found that 5 weeks post-fracture the Brtl/+ fractured bones had a significant increase in energy to failure compared to intact contralateral bones, suggesting the callus they produced is actually stronger than their intact bone.…”
Section: Discussionmentioning
confidence: 97%
“…Brtl/+ recapitulates many of the phenotypic features of pediatric OI including small size, impaired remodeling, reduced trabecular and cortical bone mass, altered bone matrix structure, and impaired fracture mechanics (2023). As such, Brtl/+ has been used to explore multiple clinically relevant questions including fracture repair (24), bisphosphonate treatment (25), and cell therapies (26). …”
Section: Introductionmentioning
confidence: 99%
“…Hardness and indentation modulus appear to be independent of mineral/matrix and carbonate/phosphate ratios until substantial amounts of mineral are laid down, although the authors fit their entire data set to straight lines. 47 There are a few studies of the correlation between biomechanical parameters and Raman spectroscopic composition parameters in mouse models of disorders, including osteogenesis imperfect (OI) [48][49][50][51] and osteoporosis, 52 as well as on the effects of knocking out matrix proteinase, 53 transcription factor 54 and noncollagenous proteins. [55][56][57][58][59][60][61][62] These are discussed in the following sections.…”
Section: Animal Age Effectsmentioning
confidence: 99%
“…50 Oim/oim mouse has been used to demonstrate composition differences between male and female mice, 49 increased disorder of collagen and mineral by polarized Raman 19 and noninvasive measurements by time-resolved Raman spectroscopy 63 and SORS. 34 Recent work with tissue from human OI patients has confirmed increased mineral/matrix ratio, decreased crystallinity and both a shift in amide I wavenumber and a decrease in amide I intensity, itself consistent with increased mineral/matrix ratio.…”
Section: Osteogenesis Imperfectamentioning
confidence: 99%